A new topological insulator built from quasi one‐dimensional atomic ribbons. Issue 2 (18th December 2014) - Schönherr, Piet; Zhang, Shilei; Liu, Yuanqian; Kusch, Patryk; Reich, Stephanie; Giles, Terence; Daisenberger, Dominik; Prabhakaran, Dharmalingam; Chen, Yulin; Hesjedal, Thorsten
<x xml:space="preserve">Abstract</x> A novel topological insulator with orthorhombic crystal structure is demonstrated. It is characterized by quasi one‐dimensional, conducting atomic chains instead of the layered, two‐dimensional sheets known from the established Bi2(Se, Te)3 system. The Sb‐doped Bi2Se3 nanowires are grown in a TiO2‐catalyzed process by chemical vapor deposition. The binary Bi2Se3 is transformed from rhombohedral to orthorhombic by substituting Sb on ∼38% of the Bi sites. Pure Sb2Se3 is a topologically trivial band insulator with an orthorhombic crystal structure at ambient conditions, and it is known to transform into a topological insulator at high pressure. Angle‐resolved photoemission spectroscopy shows a topological surface state, while Sb doping also tunes the Fermi level to reside in the bandgap. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)